Milk fatty acids as indicators of delayed commencement of luteal activity in dairy cows in early lactation. Issue 4 (12th January 2023) - Ntallaris, Theodoros; Båge, Renée; Karlsson, Johanna; Holtenius, Kjell
Abstract: Excessive mobilization of adipose reserves due to severe negative energy balance in early lactation may be detrimental to dairy cow fertility at individual and herd level. Reproductive efficiency is one of the main factors influencing herd profitability and a strategy for early detection and management of cows with delayed resumption of cyclicity will result higher conception rate, decreased proportion of cows with extended lactation, fewer inseminations per conception and lower culling rates due to reproductive disorders. Using two groups of dairy cows (Holstein n  = 37, Swedish Red breed [SRB] n  = 49), we investigated potential differences between cows with different commencement of luteal activity (CLA) and the feasibility of using milk fatty acids (MFAs) as predictors of delayed CLA. Milk samples for progesterone analysis were collected twice weekly during the first six weeks in milk. The concentrations of the MFAs C14:0, C16:0, C18:0 and C18:1 cis‐9 in milk (g/100 g milk) and in milk fat (g/100 g fat) were analysed by Fourier transform infrared spectroscopy and individual MFA profiles were calculated by weeks in milk. Commencement of luteal activity was defined as the first day with milk progesterone concentrations >3 ng/ml at two successive measurements. The study population was categorized as early ( n  = 42) or late ( n  = 44) CLA, using the median value of 21 DIM as the cut‐off. Analysis of the data revealed that CLA was correlated with the proportion of some specific MFAs, where cows with delayed CLA had lower IGF‐1 (92.9 ± 7.9 vs. 114.1 ± 7.9 ng/ml; p  = .05) and C14:0 levels (10.4 ± 0.2 vs. 11.5 ± 0.2 g/100 fat; p  < .01) and higher C18:0 (9.6 ± 0.2 vs. 8.9 ± 0.6 g/100 fat; p  < .01) and C18:1 cis‐9 levels (24.9 ± 0.4 vs. 23.5 ± 0.4 g/100 fat; p  < .05). Delayed CLA (mean 34 days) was predictable for approximately 80% of cows based on C18:0 or C18:1 cis‐9 concentrations in week 2 postpartum. Overall, MFAs (C18:0 and C18:1 cis‐9) as biomarkers were better indicators than beta‐hydroxybutyrate or non‐esterified fatty acids in early detection of cows with delayed or normal CLA. The MFA concentrations in milk samples from cows in early lactation can thus be used as a non‐invasive method to identify cows at risk of delayed CLA, acting as potential biomarkers for future reproductive performance.